Programmable Biopolymers for Advancing Biomedical Applications of Fluorescent Nanodiamonds. (8th October 2015) - Wu, Yuzhou; Ermakova, Anna; Liu, Weina; Pramanik, Goutam; Vu, Tran Minh; Kurz, Andrea; McGuinness, Liam; Naydenov, Boris; Hafner, Susanne; Reuter, Rolf; Wrachtrup, Joerg; Isoya, Junichi; et al.
Abstract : A versatile biopolymer platform for advancing nanodiamonds (NDs) as unique magnetooptic materials for biomedical applications is presented here. Precision biopolymer coatings are designed by chemical reprogramming the functionalities of serum albumin via a straightforward synthesis protocol. Such biopolymers offer high biocompatibility and precise modification with various functional entities due to the large number of available reactive amino acid residues. Premodification of these biopolymers provides a convenient approach to customized surface functionalization of NDs. As an example, the anticancer drug doxorubicin (DOX) is conjugated to the biopolymer with high reproducibility and full characterization. The biopolymer‐coated NDs reveal excellent colloidal stabilities in all physiological media tested, even after loading with high numbers of hydrophobic DOX. The intracellular distribution of NDs and DOX is analyzed in living cells by recording the fluorescence spectra in different cellular compartments, which proves efficient intracellular release of DOX from the carrier. Studies in vitro as well as in a chick tumor xenograft model reveal efficient antitumor effects. The facile and versatile biopolymer coating strategy reported herein will greatly accelerate the availability of customized NDs with reliable and reproducible features to exploit their great potential in single molecular bioimaging, in vivo biosensing, and high resolution quantum optics. Abstract : A versatile biopolymer platform for advancing fluorescent nanodiamonds as unique magnetooptic materials for biomedical applications is reported. The biopolymer coatings are designed by chemical reprogramming the functionalities of albumin, which offer high biocompatibility and precise modification with various functional entities. The biopolymer coated nanodiamonds reveal excellent colloidal stabilities even after loading high numbers of hydrophobic doxorubicin for drug delivery.